2018
DOI: 10.1002/ps.5087
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐resistance to diflufenican and picolinafen and its inheritance in oriental mustard (Sisymbrium orientale L.)

Abstract: Resistance to diflufenican and picolinafen in the P40 population is likely conferred by Leu-498-Val and Glu-425-Asp mutations in the PDS gene. Inheritance of resistance to these herbicides is managed by a single dominant gene. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The results demonstrated that resistance to PDS‐inhibiting herbicides in this R population is not due to mutation or amplification of the target‐site PDS gene. Thus, this R wild radish population does not have target‐site resistance, in contrast to other PDS‐inhibiting herbicide R weed populations that exhibit target‐site based resistance mechanisms …”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The results demonstrated that resistance to PDS‐inhibiting herbicides in this R population is not due to mutation or amplification of the target‐site PDS gene. Thus, this R wild radish population does not have target‐site resistance, in contrast to other PDS‐inhibiting herbicide R weed populations that exhibit target‐site based resistance mechanisms …”
Section: Discussionmentioning
confidence: 89%
“…For example, resistance to the PDS‐inhibiting herbicide fluridone was reported in H. verticillata due to target PDS gene mutations (Arg304‐Ser, Arg304‐Cys and Arg304‐His) . Most recently, high levels of resistance (up to 237‐fold) to diflufenican and picolinafen were reported in Sisymbrium orientale , which are endowed by the PDS gene mutations Leu498‐Val alone and Glu425‐Asp plus Leu498‐Val, respectively …”
Section: Introductionmentioning
confidence: 99%
“…In this study, malathion application ruled out Cyt-P450 metabolic-based resistance to diflufenican in the R C. bonariensis population. Most cases of resistance to PDS inhibitors have involved target site mutations in the PDS gene, , suggesting that the diflufenican resistance of the R C. bonariensis population might be based on TSR mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, malathion application ruled out Cyt-P450 metabolicbased resistance to diflufenican in the R C. bonariensis population. Most cases of resistance to PDS inhibitors have involved target site mutations in the PDS gene, 47,48 suggesting that the diflufenican resistance of the R C. bonariensis population might be based on TSR mechanisms. Because the R C. bonariensis population showed a response to 2,4-D similar to that of the S population after treatment with malathion, it was clear that metabolic resistance mediated by Cyt-P450 was the only mechanism against the phytotoxic action of 2,4-D.…”
Section: Discussionmentioning
confidence: 99%
“…A double-substitution Glu-425-Asp + Leu-498-Val was first observed in S. orientale from Australia [83]. Dose–response revealed a resistant phenotype to diflufenican and picolinafen, which are both pyridinecarboxamides.…”
Section: Summary By Herbicide Groupmentioning
confidence: 99%